2011
DOI: 10.1007/s00213-010-2158-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a novel histamine subtype-3 receptor inverse agonist and modafinil on EEG power spectra during sleep deprivation and recovery sleep in male volunteers

Abstract: Rationale: Histamine and dopamine contribute to the maintenance of wakefulness.Objective: Exploratory analysis of the effects of 10 and 50 mg of MK-0249, a novel histamine subtype-3 receptor inverse agonist, and 200 mg of modafinil, a presumed dopaminergic compound, on EEG power spectra during sleep deprivation and subsequent recovery sleep. Methods: 25 healthy men were recruited to a double-blind placebocontrolled cross-over design. EEG power spectra, an electrophysiological marker of changes in sleepiness an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 25 publications
5
21
0
Order By: Relevance
“…1) and have been used in several clinical studies (13,14,19). Both compounds have a nanomolar affinity for H3 receptors and are highly specific for H3 receptors (inhibition constant is .10 mM for H1, H2, and H4, and no other off-target activities below 1 mM).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1) and have been used in several clinical studies (13,14,19). Both compounds have a nanomolar affinity for H3 receptors and are highly specific for H3 receptors (inhibition constant is .10 mM for H1, H2, and H4, and no other off-target activities below 1 mM).…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the current study was to evaluate the biodistribution, dosimetry, and quantification of 11 C-MK-8278 in humans and to determine its utility in clinical occupancy studies of 2 novel histamine H3 IAs, MK-0249 (13,14,19) and MK-3134 (20). Open-label, 2-period, multipanel studies were done to investigate occupancies of single oral doses at the time of approximately maximum occupancy (approximate plasma T max ) in the target range of 50%-90% brain H3 RO.…”
mentioning
confidence: 99%
“…Narcolepsy is characterized by excessive diurnal sleepiness and can occur alone or as part of other neurologic disorders (e.g., Parkinson's disease). On the basis of the wake-inducing properties of H 3 receptor blockade, pitolisant (45) was developed, together with an apparent ideal pharmacokinetic profile, where a once-aday dose maintains attention over the day, but, importantly, allows individuals to sleep at night (Iannone et al, 2010;James et al, 2011;Schwartz, 2011). Preclinical studies have also suggested the lack of drug abuse liability Histamine Receptors for pitolisant in rodent and primate models, in contrast to modafinil (Uguen et al, 2013).…”
Section: F Clinical Pharmacologymentioning
confidence: 99%
“…response to modafinil (Nagels et al, 2007); and after sleep deprivation in healthy subjects, modafinil partly normalized both the increased delta and theta activity, and the reduced alpha and beta activity, that were each observed on placebo (James et al, 2011).…”
Section: Discussionmentioning
confidence: 92%